Wound swab and wound biopsy yield similar culture results. Issue 2 (19th May 2018) - Haalboom, Marieke; Blokhuis‐Arkes, Miriam H.E.; Beuk, Roland J.; Klont, Rob; Guebitz, Georg; Heinzle, Andrea; van der Palen, Job
Abstract : The question remains whether wound swabs yield similar culture results to the traditional gold standard, biopsies. Swabs are not invasive and easy to perform. However, they are believed to capture microorganisms from the surface rather than microorganisms that have invaded tissue. Several studies compared swabs and biopsies using different populations and sampling methods, complicating the ability to draw conclusions for clinical practice. This study aimed to compare swab and biopsy in clinical practice, by including a variety of wounds and using standard sampling and culture procedures. Swabs (Levine technique) and biopsies were taken for microbiological culture in a standardized manner from the same location of one wound for each patient. Statistical analyses were performed to determine overall agreement, and observed agreement and kappa for specific microorganisms. A variety of wounds of 180 patients from different healthcare facilities in The Netherlands were included. Skin flora was more frequently cultured from swabs, resulting in similar recovery rates when excluding skin flora (1.34 vs 1.35). Swabs were able to identify all microorganisms cultured from biopsies in 131 wounds (72.8%) wounds. Most frequently identified organisms were Staphylococcus aureus, Pseudomonas aeruginosa, and beta‐haemolytic streptococci species . Observed agreement and kappa for these organisms varied between 87.2 and 97.8% and 0.73 and 0.85, respectively. This study demonstrates that swabs and biopsies tend to yield the same culture results when taken from the same location. For frequently occurring microorganisms, agreement between the two methods was even higher. Therefore, there seems to be no direct need for invasive biopsy in clinical practice.